Autosomal dominant variants in FOXJ1 causing primary ciliary dyskinesia in two patients with obstructive hydrocephalus. Issue 7 (15th June 2021) - Shapiro, Adam J.; Kaspy, Kimberley; Daniels, M. Leigh Ann; Stonebraker, Jaclyn R.; Nguyen, Van‐Hung; Joyal, Lyne; Knowles, Michael R.; Zariwala, Maimoona A.
Abstract: Background: Primary ciliary dyskinesia (PCD) is a mostly autosomal recessive, genetic disease of abnormal motile cilia function, resulting in bronchiectasis, infertility, organ laterality defects, and chronic otolaryngology disease. Though motile, ependymal cilia influencing cerebrospinal fluid flow in the central nervous system share many aspects of structure and function with motile cilia in the respiratory tract, hydrocephalus is rarely associated with PCD. Recently, pathogenic variants in FOXJ1 (Chr 17q25.1) were identified causing PCD associated with hydrocephalus, reduced respiratory cilia number, axonemal microtubule disorganization, and occurring in a de novo, autosomal dominant inheritance pattern. Method: Two patients with chronic oto‐sino‐pulmonary disease and hydrocephalus underwent candidate testing of FOXJ1 . Coding region and splice junctions were sequenced and analyzed under the auspices of Genetic Disorders of Mucociliary Clearance Consortium. Results: Upon sequencing of the entire coding region and splice‐junctions, heterozygous, pathogenic variants in FOXJ1 were discovered in exon 3 of two patients: an 11‐month‐old female with situs inversus totalis (NM_001454.4: c.945delC (p.Phe315Leufs*18)) and a 51 year‐old male, post‐double lung transplantation (NM_001454.4: c.929_932delACTG (p.Asp310Glyfs*22)). FOXJ1 variants were not detected in the available parents and the siblings of these probands. Conclusion: FOXJ1 pathogenic variants cause PCD in a de novo, autosomal dominant inheritance pattern, and are associated with hydrocephalus. Physicians treating patients with hydrocephalus and chronic oto‐sino‐pulmonary disease should be aware of this PCD association and test for FOXJ1 variants. Abstract : Variants in FOXJ1 are a rare cause of respiratory ciliary dysfunction and hydrocephalus, but few cases have been previously illustrated. We report 2 cases of primary ciliary dyskinesia (PCD) with hydrocephalus, both caused by de novo, autosomal dominant, variants in FOXJ1. FOXJ1 should be examined in patients with hydrocephalus and classic PCD symptoms of chronic oto‐sino‐pulmonary disease, neonatal respiratory distress, and organ laterality defects.